Recent progress and debates in molecular physiology of Na+ uptake in teleosts - Shih, Shang-Wu; Yan, Jia-Jiun; Chou, Ming-Yi; Hwang, Pung-Pung (Frontiers in Marine Science, 2023)
How teleosts take up Na+ from the surrounding freshwater (FW) as well as the underlying mechanisms associated with this process have received considerable attention over the past 85 years. Owing to an enormous ion gradient between hypotonic FW and fish body fluids, teleosts gills have to actively absorb Na+ (via ionocytes) to compensate for the passive loss of Na+. To date, three models have been proposed for Na+ uptake in teleost ionocytes, including Na+/H+ exchanger (NHE)-mediated, acid-sensing ion channel (ASIC)-mediated, Na+-Cl- co-transporter (NCC)-mediated pathways. However, some debates regarding these models and unclear mechanisms still remain. To better understand how teleosts take up Na+ from FW, this mini-review summarizes the main progress and related regulatory mechanisms of Na+ uptake, and discusses some of the challenges to the current models.